Early Laboratory Predictors for Necessity of Renal Replacement Therapy in Patients With Spontaneous Deep-Seated Intracerebral Hemorrhage - Schenk, Lorena M.; Schneider, Matthias; Bode, Christian; Güresir, Erdem; Junghanns, Christoph; Müller, Marcus; Putensen, Christian; Vatter, Hartmut; Zimmermann, Julian; Schuss, Patrick; Lehmann, Felix (Frontiers in Neurology, 2021)
The need for continuous renal replacement therapy (CRRT) in patients with deep-seated intracerebral hemorrhage (ICH) requires sustained intensive care and often postpones further rehabilitation therapy. Therefore, an early identification of patients at risk is essential. From 2014 to 2019, all patients with deep-seated ICH who were admitted to intensive care for > 3 days were included in the further analysis and retrospectively reviewed for the need for CRRT. All patients underwent CRRT with regional citrate anticoagulation for continuous veno-venous hemodialysis (CVVHD). Outcome was evaluated after 3 months using the modified Rankin scale. A multivariate analysis was performed to identify potential predictors for CRRT in patients with deep-seated ICH. After applying the inclusion criteria, a total of 87 patients with deep-seated spontaneous ICH were identified and further analyzed. 21 of these patients developed early acute kidney injury (AKI; 24%) during the first 48 hours after admission. During treatment course, CRRT became necessary in 9 patients suffering from deep-seated ICH (10%). The multivariate analysis revealed “development of AKI during the first 48 hours” (p=0.025, OR 6.1, 95% CI 1.3-29.8) and “admission PCT value >0.5µg/l” (p=0.02, OR 7.7, 95% CI 1.4-43.3) as independent and significant predictors for CRRT in patients with deep-seated ICH. Elevated serum levels of procalcitonin on admission as well as early development of acute renal injury are independent predictors of the need for renal replacement therapy in patients with deep-seated intracerebral bleeding. Therefore, further research is warranted to identify these vulnerable patients as early as possible to enable adequate treatment.